Comparison of "in vitro" culture of Toxoplasma gondii RH strain in Hep-2 and Vero cell lines - Cortés, Liliana Jazmín; González, Carlos Ariel; Ballesteros, Daniel Alexander; Benavides, Yeimy Lizeth; Zipa Cely, Alexandra; Castillo, María Carlina (Universidad y Salud, 2013)
Introduction: Toxoplasmosis is a zoonosis caused by Toxoplasma gondii, which is an obligate intracellular parasite capable of replicate itself in all nucleated cells, allowing their isolation and maintenance in cell culture. Objective: To compare cultivation Toxoplasma gondii (RH) in Hep-2 cells and Vero employed to spread parasitic. Methods: The conditions were optimized for cultivation of Toxoplasma gondii (RH) in Vero and Hep-2 cells lines, 500.000 and 1.000.000cel./mm3 were seeded and 1.000.000 and 2.000.000taq/mm3 were infected respectively, a track to determine cell invasion, percentage of rosettes and viability and efficiency of tachyzoites was made until the 120 hours. Results: After 48 hours of incubation, 90% of parasite invasion was evident in both cell lines as well as the largest count rosettes. At 120 hours higher counts of extracellular tachyzoites and a higher rate of performance of 185.9 in Hep-2 cells at concentration of 1.000.000taq/mm3 and 500.000cel./mm3 were obtained. Average parasite viability over 80 % was obtained for both cell lines. Conclusions: Higher parasitic performance was obtained viable in Hep-2 cells, so that this cell line can be considered as the preferred model for the propagation and maintenance of T. gondii (RH).